PENGARUH GAYA KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI PADA PEGAWAI DI KANTOR SEKRETARIAT DAERAH KABUPATEN KEEROM PROVINSI PAPUA - Ali, Muhammad (JI@P, 2017)
In this research study want to view how relationship between leadershipstyle and Organizational culture in regional secretariat office Keeromregency province of Papua. Leadership style is an overall pattern of aleaders actions both visible and invisible by his subordinates as seen fromideal factors participative style, nurturant style, authoritarian style,bureaucratic style and task. While organization culture a is A pattern ofshared basic assumptions that the group learned as it solved its problems ofexternal adaptation and internal integration, that has worked well enough tobe considered valid and, therefore, to be taught to new members as thecorrect way you perceive, think, and feel in relation to those problems,factors of distance of management, work partner trust, regularity, enmity andintegration. The method used is the kind of explanatory research-analyticapproach study of 150 employee as samples served in regional secretariatoffice Keerom regency province of Papua and analytical test data analysispath diagram / confirmatory factor analysis of Structural Equation Model(SEM). The results showed leadership style positive and significant effect onorganization culture (CR =2,155 & p = 0.031), factor participative style,nurturant style and bureaucratic style have a strong effect on leadershipstyle and factor work partner trust have a strong effect on organizationculture.Keywords: Leadership Style, Organizational Culture, and Structural EquationModel(SEM).